Rasionalisasi Pada Film “Merindu Cahaya De Amstel” - Nasichah; Aditya Firmansyah; Nur Syarifah; Raudhatul Ikrimah (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
This study analyzes the film "Merindu Cahaya de Amstel" (MCDA) through the lens of rationalization, as seen in communication psychology and dakwah. The primary focus is on understanding how characters in the film rationalize their decisions and actions, particularly in the context of religious and cultural influences. The research employs a qualitative approach, utilizing film analysis to explore themes of cognitive dissonance, justification, and the role of religious teachings in shaping rationalization processes. The findings reveal that the characters' rationalizations are deeply intertwined with their personal beliefs and societal norms, highlighting the complex interplay between individual psychology and broader cultural values.